Rural Development in Haiti : Challenges and Opportunities - Coello, Barbara; Oseni, Gbemisola; Savrimootoo, Tanya; Weiss, Eli (World Bank, Washington, DC, 2015)
The objective of this report is to examine the linkages between rural economic activity, food insecurity and poverty in Haiti as a means of determining the barriers to rural development. The analysis draws on a newly available set of house-hold level living standards measurement data collected in 2012 (ECVMAS). About 70.7 percent of all rural households are poor, and education levels are low with an average of 2.8 years of education for the household head. Agriculture dominates economic activity (78 percent of all households are involved in agricultural activities), although almost 25 percent of the agricultural households supplement their agricultural income by engaging also in some type of nonfarm activity. Overall nonfarm activity participation (including households that engage in agricultural activities and households that do not) is reported at 46 percent. Nonfarm activities can be related to agriculture upstream (input supply) or downstream (value-adding and processing), or they can be unrelated to the sector (retailing). This report identifies the main factors of production that correlate with increased productivity in the agricultural sector and examines the determinants of nonfarm participation, poverty and food security within rural Haiti. The information and analysis presented in this report point to two priority areas for rural development interventions in Haiti: (i) promoting diversification of livelihoods sources among rural households, and (ii) improving the performance of rural markets for inputs and outputs.